Trichodysplasia spinulosa: a polyomavirus infection specifically targeting follicular keratinocytes in immunocompromised patients. (1st March 2016) - Rouanet, J.; Aubin, F.; Gaboriaud, P.; Berthon, P.; Feltkamp, M.C.; Bessenay, L.; Touzé, A.; Nicol, J.T.J.; Franck, F.; D'Incan, M.
Summary: Trichodysplasia spinulosa (TS) is a rare skin disease, caused by a specific polyomavirus, occurring in immunocompromised patients. The pathophysiological mechanisms of TS are not yet fully understood. By using polymerase chain reaction and skin biopsy immunostaining we report evidence, in a paediatric case, of follicular keratinocytes being the primary target of trichodysplasia spinulosa‐associated polyomavirus.